Niat Konsumsi Wisatawan Terhadap Kuliner Tradisional Gudeg di Sentra Kuliner Wijilan, Yogyakarta Dalam Kerangka Theory of Planned Behavior - Sahlit Sugesti; Enny Mulyantari; Setyo Prasiyono Nugroho; Slamet Supriyanto (Journal of Tourism and Economic, 2025)
This research seeks to assess the psychological elements that affect tourists' intentions to try traditional cuisine, utilizing the Theory of Planned Behavior (TPB) framework. It specifically examines the Gudeg Wijilan Culinary Center in Yogyakarta, which serves as a key representation of Javanese food culture. A quantitative explanatory approach was used, involving a survey of 100 tourists selected through accidental sampling. The research instrument included five primary TPB variables: attitude, subjective norm, perceived behavioral control, consumption intention, and actual behavior. Data analysis employed multiple linear regression and path analysis to investigate both direct and indirect relationships among the variables. The findings reveal that all TPB components positively and significantly impact tourists' intentions to consume traditional cuisine, with subjective norm being the most influential factor, followed by attitude and perceived behavioral control. Furthermore, actual behavior was identified as a partial mediator, indicating that tourists’ firsthand experiences consuming gudeg enhanced the connection between psychological factors and their intention to act. These results underscore that decisions made by tourists are influenced by personal assessments, social factors, and perceptions of accessibility to traditional cuisine. This study's originality lies in applying the TPB model to a specific traditional culinary context and including actual behavior as a mediating variable when analyzing tourists’ intentions. It contributes to the theoretical understanding of tourist consumption behavior and provides actionable insights for destination managers to create more effective marketing strategies rooted in consumer psychology and tourist experiences.